Seroprevalence of Trichinella spp. infection in bank voles (Myodes glareolus) – A long term study. (August 2019) - Grzybek, Maciej; Cybulska, Aleksandra; Tołkacz, Katarzyna; Alsarraf, Mohammed; Behnke-Borowczyk, Jolanta; Szczepaniak, Klaudiusz; Strachecka, Aneta; Paleolog, Jerzy; Moskwa, Bożena; Behnke, Jerzy M.; Bajer, Anna
Abstract: Rodents play an important role as reservoir hosts of zoonotic diseases. As a component of our long-term programme of monitoring parasitic infections in bank vole populations in three ecologically similar sites in NE Poland, we screened blood samples for signs of a serological response to the presence of Trichinella spp. The overall seroprevalence of Trichinella spp. was 1.52%, but prevalence was largely concentrated in one of our three study sites and confined to the oldest individuals in the study. Seroprevalence of Trichinella spp. did not differ between the sexes. Although a local prevalence of 1.52% may seem low, when this is extrapolated to the national population of bank voles in peak years, perhaps numbering hundreds of millions of animals, the number of infected bank voles on a country wide scale is likely to be huge. Our results suggest that bank voles may be reservoirs of Trichinella spp. However, on the basis of our results we consider their importance as epidemiologically significant hosts for Trichinella spp. to be moderate and their role in this context to require further investigation. Graphical abstract: Image 1 Highlights: Seroprevalence of Trichinella spp. was relatively stable between the years of study. There was significant variation of Trichinella spp. seroprevalence between study sites maintained over nine years study. Trichinella spp. seroprevalence was highest in the oldest bank voles and was essentially identical in both sexes.